Animal signals and emotion in music: coordinating affect across groups - Bryant, Gregory A. (Frontiers in Psychology, 2013)
Researchers studying the emotional impact of music have not traditionally been concerned with the principled relationship between form and function in evolved animal signals. The acoustic structure of musical forms is related in important ways to emotion perception, and thus research on nonhuman animal vocalizations is relevant for understanding emotion in music. Musical behavior occurs in cultural contexts that include many other coordinated activities which mark group identity, and can allow people to communicate within and between social alliances. The emotional impact of music might be best understood as a proximate mechanism serving an ultimately social function. Here I describe recent work that reveals intimate connections between properties of certain animal signals and evocative aspects of human music, including 1) examinations of the role of nonlinearities (e.g., broadband noise) in nonhuman animal vocalizations, and the analogous production and perception of these features in human music, and 2) an analysis of group musical performances and possible relationships to nonhuman animal chorusing and emotional contagion effects. Communicative features in music are likely due primarily to evolutionary byproducts of phylogenetically older, but still intact communication systems. But in some cases, such as the coordinated rhythmic sounds produced by groups of musicians, our appreciation and emotional engagement might be due to the operation of an adaptive social signaling system. Future empirical work should examine human musical behavior through the comparative lens of behavioral ecology and an adaptationist cognitive science. By this view, particular coordinated sound combinations generated by musicians exploit evolved perceptual response biases—many shared across species—and proliferate through cultural evolutionary processes.